2018
DOI: 10.1111/ctr.13179
|View full text |Cite
|
Sign up to set email alerts
|

First‐line choice for severe aplastic anemia in children: Transplantation from a haploidentical donor vs immunosuppressive therapy

Abstract: We retrospectively compared the outcomes of children with severe aplastic anemia (SAA) who received immunosuppressive therapy (IST) or who underwent hematopoietic stem cell transplantation (HSCT) from a haploidentical donor (HID), between 2007 and 2016. A total of 52 children with SAA under the age of 17 years were initially treated with IST (n = 24) or haploidentical HSCT (n = 28) as first-line treatment. The estimated 10-year overall survival was 73.4 ± 12.6% and 89.3 ± 5.8% in patients treated with IST or H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
(147 reference statements)
3
20
0
Order By: Relevance
“…Our prior study suggested the noninferiority of MUDs to MSDs when the pretransplant conditions were well matched in this high-resolution human leukocyte antigen (HLA) typing era, and several studies have supported our analysis [1, 4, 5]. Therefore, alloHSCT from MUDs and haplo-identical family donors is a plausible strategy for severe AA patients without an MSD [6, 7]. AlloHSCT cases using PBSCs surpass those treated using BM.…”
Section: Introductionsupporting
confidence: 56%
“…Our prior study suggested the noninferiority of MUDs to MSDs when the pretransplant conditions were well matched in this high-resolution human leukocyte antigen (HLA) typing era, and several studies have supported our analysis [1, 4, 5]. Therefore, alloHSCT from MUDs and haplo-identical family donors is a plausible strategy for severe AA patients without an MSD [6, 7]. AlloHSCT cases using PBSCs surpass those treated using BM.…”
Section: Introductionsupporting
confidence: 56%
“…This is consistent with the present controversial treatment situation. In China, HID-HSCT has been advocated as a rst-line treatment for children with AA [19], but in the United States and Europe, HID-HSCT is regarded as an experimental treatment for the relatively limited number of cases reported with unknown long-term effects of complicated regimens and a mismatched immune system. In addition, we observed a great disparity in FFS for patients treated with allo-HSCT versus IST.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported the outcomes of AA patients treated with rst-line allo-HSCT or IST [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The allo-HSCT group was divided into two subgroups: BMT-MRD and BMT-MUD.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…All studies reported the outcomes of AA patients treated with first-line allo-HSCT or IST [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The allo-HSCT group was divided into two subgroups: BMT-MRD and BMT-MUD.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…This is consistent with the present controversial treatment situation. In China, HID-HSCT has been advocated as a first-line treatment for children with AA [24], but in the United States and Europe, HID-HSCT is regarded as an experimental treatment for the relatively limited number of cases reported with unknown long-term effects of complicated regimens and a mismatched immune system. In addition, we observed a great disparity in FFS for patients treated with allo-HSCT versus IST.…”
Section: Disscussionmentioning
confidence: 99%